1972
DOI: 10.1111/j.1748-1716.1972.tb05174.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of the Prostaglandin System in the Rabbit Renal Papilla

Abstract: ANGG~RD, E., S. 0. BOHMAN, J. E. GRIFFIN 111, C. LARSSON and A. B. MAUNS-BACH. Subcellular localization of the prostaglandin system in the rabbit renal papilla. Acta physiol. scand. 1972. 84. 231-246. The occurrence of prostaglandins (PG), prostaglandin precursor acids, prostaglandin synthetase and 15-hydroxy prostaglandin dehydrogenase was studied in subcellular fractions isolated from homogenates of rabbit renal papilla by sucrose density gradient centrifugation. The investigated fractions were lipid drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
1
2

Year Published

1974
1974
1992
1992

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(31 citation statements)
references
References 39 publications
4
24
1
2
Order By: Relevance
“…There is general agreement that prostaglandins are not stored within cells (23)(24)(25)(26). Prostaglandin synthesis is rapid, apparently limited by substrate availability and hence turnover is extensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is general agreement that prostaglandins are not stored within cells (23)(24)(25)(26). Prostaglandin synthesis is rapid, apparently limited by substrate availability and hence turnover is extensive.…”
Section: Discussionmentioning
confidence: 99%
“…These precautions may explain why the values in Table I are much lower than previously reported (5). Therefore if appropriate care is taken to avoid significant postmortem tissue synthesis, tissue levels are quite low and may be a poor reflection of in vivo synthesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…1 Abbreviationis used in this paper: CPBA, competitive cating little direct excretory clearance of the primary prostaglandins from the circulation. The kidney itself, however, is a prime site of prostaglandin synthesis (3)(4)(5), and it was conceived that PG synthesized in the kidney might diffuse directly into the urine. Certainly some substances such as tryptamine (6) and cyclic AMP (7) appear in the urine totally or in part as a reflection of their intrarenal synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Initially it was believed that their activity was largely confined to the renal papilla and medulla where all species studied showed a rich source of prostaglandin synthetase (Anggard et al, 1972;Crowshaw & McGiff, 1973;Larsson & Anggard 1973;Blackwell et al, 1975;Dunn 1976). However, it was also shown that the renal cortex could synthesize small amounts of prostaglandin E2 (PGE2) and PGF2,,: (Larsson et al, 1974;Dunn 1976;Pong & Levine 1976).…”
Section: Introductionmentioning
confidence: 99%